THE ROLE OF THE EXTERNAL AUDITOR IN KNOWING THE INTERNATIONAL STANDARD (265) AND ACHIEVING GOVERNANCE IN ECONOMIC UNITS - Kanar Jassim Mohammed; Prof. Dr. Sabiha Barzan Farhoud (American Journals, 2022)
This research aims to know the international auditing standard (265) to implement the role of the external auditor, governance in economic units, so the research problem is in light of the following question: What is the role of the external auditor in the concept of international application (265) to achieve governance in economic units, private highlights the importance of The research is of the importance of a key role in the field of international knowledge (265) As for the research methods: My methodology has been adopted: The first approach is in deductive: Second is the inductive approach: 2018 and then you include it in the governance of the organization you manage, which you manage in the governance of units Economic.
Keywords: external auditor, international auditing standard (265), governance.